Expert Python Programming : Become a Master in Python by Learning Coding Best Practices and Advanced Programming Concepts in Python 3.7 - Jaworski, Michał (Packt Publishing, Limited, 2019)
Expert Python Programming, Third Edition is a collection of valuable tips that will help you build robust and scalable applications in Python. These will help you become confident at solving challenging programming problems effectively.
Functional-style features of Python
Includes index.
Keywords: Python (Computer program language); Application software -- Development.; Python (Langage de programmation); Logiciels d'application -- Développement.; Application software -- Development